PENERAPAN INTERVENSI SLOW STROKE BACK MASSAGE UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI - Anisa Ismawanti; Mulyaningsih; Listyorini, Dewi (Lasalle Health Journal, 2025)
Introduction: Hypertension is one of the non-communicable diseases that contribute greatly to morbidity and mortality rates in the world, including in Indonesia. The management of hypertension is not only limited to pharmacological therapy, but also involves non-pharmacological interventions such as Slow Stroke Back Massage (SSBM) therapy, which has been proven effective in lowering blood pressure. Objective: Knowing the results of the application of Slow Stroke Back Massage intervention in reducing blood pressure in patients with hypertension at RSUD Kartini Karanganyar. Methods : This study used a descriptive approach with a case study design. The Slow Stroke Back Massage intervention was carried out on hypertensive patients who were treated in Cempaka Room 3. Blood pressure was measure before and after the intervention to determine the effectiveness of therapy. Results : The application results showed a significant decrease in systolic and diastolic blood pressure after the Slow Stroke Back Massage intervention. This therapy provides a relaxing effect that helps vasodilate blood vessels so that blood pressure decreases. Conclusions: Slow Stroke Back Massage is an effective non-pharmacological nursing intervention and can be used as a complementary therapy to reduce blood pressure in hypertensive patients. This therapy also improves patient comfort and quality of life. Keyword: Hypertension, Slow Stroke Back Massage, Blood Pressure, Non-pharmacological